Diffuse primary extra-gastrointestinal stromal tumor of the peritoneum: A rare case report. Issue 40 (2nd October 2020) - Lu, Liang-ji; Xu, Xiao-pei; Dong, Fei; Min, Jie
Abstract: Rationale: Gastrointestinal stromal tumors that present outside the gastrointestinal tract are known for extra-gastrointestinal stromal tumors (EGISTs) and they share the same morphological and immunohistochemical characteristics with gastrointestinal stromal tumors. Here we report a rare case of diffuse primary EGIST arising at peritoneum. Patient concerns: A 57-year-old male presented to the hospital with abdominal pain and right lower abdominal tenderness. Diagnosis: The core needle puncture biopsy showed epithelial-like cells and the nuclei were ovoid and focally elongated. Immunohistochemical examination was consistent with a primary EGIST of the peritoneum. Interventions: The patient was treated with Imatinib mesylate. Outcomes: Five months later, there is no complication resulting from treatment. The follow-up abdominal contrast-enhanced CT showed the lesion was significantly decreased in size, and was evaluated as partial response. The patient continued the treatment with Imatinib as prescribed by the oncologist. Lessons: EGISTs are rare and should be considered in the differential diagnosis of the peritoneal tumors and immunohistochemistry helps to confirm the diagnosis. Further study with longer follow-up is desired to characterize these uncommon tumors.